2021
DOI: 10.1126/sciadv.abb7403
|View full text |Cite
|
Sign up to set email alerts
|

Strong local, not global, controls on marine pyrite sulfur isotopes

Abstract: Understanding variation in the sulfur isotopic composition of sedimentary pyrite (δ34Spyr) is motivated by the key role of sulfur biogeochemistry in regulating Earth’s surface oxidation state. Until recently, the impact of local depositional conditions on δ34Spyr has remained underappreciated, and stratigraphic variations in δ34Spyr were interpreted mostly to reflect global changes in biogeochemical cycling. We present two coeval δ34Spyr records from shelf and basin settings in a single sedimentary system. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 100 publications
2
32
0
Order By: Relevance
“…Important output fluxes for sulfur are the burial of sulfate-evaporites (0.83 × 10 18 mol/ Myr), which has a minor isotopic fractionation, and sedimentary pyrite with a flux of 0.67 × 10 18 mol/Myr (Burke et al, 2018). Pyrite formation via microbial sulfate reduction (MSR) records up to a −70‰ sulfur isotope fractionation between sulfate and the product sulfide, (approximated by Δ 34 S; Δ 34 S = δ 34 S SO4 -δ 34 S H2S ) and thus leaves residual sulfate isotopically heavier, compared to isotopically light sulfide (Lang et al, 2020;Pasquier et al, 2021). This process occurs in anaerobic environments and is dependent on the availability of labile organic matter, reactive iron, and sulfate (Gomes & Hurtgen, 2015;Sim, 2019).…”
Section: Local and Global Redox Proxiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Important output fluxes for sulfur are the burial of sulfate-evaporites (0.83 × 10 18 mol/ Myr), which has a minor isotopic fractionation, and sedimentary pyrite with a flux of 0.67 × 10 18 mol/Myr (Burke et al, 2018). Pyrite formation via microbial sulfate reduction (MSR) records up to a −70‰ sulfur isotope fractionation between sulfate and the product sulfide, (approximated by Δ 34 S; Δ 34 S = δ 34 S SO4 -δ 34 S H2S ) and thus leaves residual sulfate isotopically heavier, compared to isotopically light sulfide (Lang et al, 2020;Pasquier et al, 2021). This process occurs in anaerobic environments and is dependent on the availability of labile organic matter, reactive iron, and sulfate (Gomes & Hurtgen, 2015;Sim, 2019).…”
Section: Local and Global Redox Proxiesmentioning
confidence: 99%
“…Since marine sulfate throughout the Phanerozoic had a significantly longer residence (10 5 -10 7 yrs) time than inter-ocean mixing timescales (10 3 yrs) and thus is homogenous throughout ocean basins, δ 34 S CAS values are generally representative of the global seawater reservoir. Pyrite sulfur (δ 34 S pyr ) isotopes, in contrast, are best used as a local proxy for MSR activity and the associated factors that control the magnitude of fractionation, such as rates of sulfate reduction, iron availability for pyrite formation, and interplays between open and closed system dynamics (Lang et al, 2020;Pasquier et al, 2021).…”
Section: Local and Global Redox Proxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, studies have shown how sulfur isotope variability may instead be controlled by sedimentary facies and diagenetic processes (Magnall et al, 2016;Pasquier et al, 2017;Marin-Carbonne et al, 2018;Bryant et al, 2019;Richardson et al, 2019;Bryant et al, 2020;Pasquier et al, 2021). For example, the progressive modification of pore fluid sulfate by MSR during diagenesis can result in strong isotopic gradients and a range of δ 34 S pyrite values, depending on the location of pyrite formation in the sediment (Canfield, 2001b;Canfield et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Important output fluxes for sulfur are the burial of sulfate‐evaporites (0.83 × 10 18 mol/Myr), which has a minor isotopic fractionation, and sedimentary pyrite with a flux of 0.67 × 10 18 mol/Myr (Burke et al., 2018). Pyrite formation via microbial sulfate reduction (MSR) records up to a −70‰ sulfur isotope fractionation between sulfate and the product sulfide, (approximated by Δ 34 S; Δ 34 S = δ 34 S SO4 – δ 34 S H2S ) and thus leaves residual sulfate isotopically heavier, compared to isotopically light sulfide (Lang et al., 2020; Pasquier et al., 2021). This process occurs in anaerobic environments and is dependent on the availability of labile organic matter, reactive iron, and sulfate (Gomes & Hurtgen, 2015; Sim, 2019).…”
Section: Introductionmentioning
confidence: 99%